PENGARUH KEPUTUSAN INVESTASI, KEBIJAKAN DIVIDEN DAN KEBIJAKAN HUTANG TERHADAP NILAI PERUSAHAAN SEKTOR PROPERTY, REAL ESTATE DAN BUILDING CONTRUCTIONS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2016-2018 - Satria Rukmana, Heru; Esa Mardiyani, Rosi (Economicus, 2020)
This study aims to determine the effect of investment decisions, dividend policy and debt policy on corporate value decisions in the property, real estate and building construction sectors for the period 2016-2018. This research uses quantitative analysis. The coefficient of determination test results where the adjusted rsquare value of the Investment Decision variable (X1), the Dividend Policy variable (X2) and the Debt Policy variable (X3) is 90.5%, which means that the deterimination coefficient value of the Investment Decision variable (X1), the Dividend Policy variable (X2) ) and the debt policy variable (X3) has a dominant factor affecting the firm value variable (Y). Based on the results of multiple linear regression, the equation Ŷ = -1.972 + 0.071 + 0.018 + 0.602 is obtained. From the results of hypothesis testing, it states that there is an influence of the Investment Decision (X1), Dividend Policy (X2) and Debt Policy (X3) on Firm Value (Y). The results of the partial t test where the significant value of the Investment Decision variable (X1) is 0.000 <0.05, the significant value of the Dividend Policy variable (X2) is 0.000 <0.05 and the significant value of the Debt Policy variable (X3) is 0.022 <0.05.